Drought and recovery effects on belowground respiration dynamics and the partitioning of recent carbon in managed and abandoned grassland. (27th May 2020) - Ingrisch, Johannes; Karlowsky, Stefan; Hasibeder, Roland; Gleixner, Gerd; Bahn, Michael
Abstract: The supply of soil respiration with recent photoassimilates is an important and fast pathway for respiratory loss of carbon (C). To date it is unknown how drought and land‐use change interactively influence the dynamics of recent C in soil‐respired CO2 . In an in situ common‐garden experiment, we exposed soil‐vegetation monoliths from a managed and a nearby abandoned mountain grassland to an experimental drought. Based on two 13 CO2 pulse‐labelling campaigns, we traced recently assimilated C in soil respiration during drought, rewetting and early recovery. Independent of grassland management, drought reduced the absolute allocation of recent C to soil respiration. Rewetting triggered a respiration pulse, which was strongly fuelled by C assimilated during drought. In comparison to the managed grassland, the abandoned grassland partitioned more recent C to belowground respiration than to root C storage under ample water supply. Interestingly, this pattern was reversed under drought. We suggest that these different response patterns reflect strategies of the managed and the abandoned grassland to enhance their respective resilience to drought, by fostering their resistance and recovery respectively. We conclude that while severe drought can override the effects of abandonment of grassland management on the respiratory dynamics of recent C, abandonment alters strategies of belowground assimilate investment, with consequences for soil‐CO2 fluxes during drought and drought‐recovery. Abstract : In a 13 C‐tracer experiment we tested whether the response of carbon (C) dynamics to drought differs between managed and abandoned grasslands. Overall, drought reduced the amount of recent C respired belowground, and rewetting triggered a pulse of soil CO2 emissions, which was strongly fueled by recent C. Compared to abandoned grasslands, managed grasslands partitioned more assimilates to root storage and less to belowground respiration under ample water supply. Drought changed the patterns of belowground C partitioning, reflecting contrasting strategies of the two grasslands to enhance drought resistance and recovery.